Pengaruh Motivasi Kerja terhadap Kinerja Karyawan - Fransiskus Ady; Djoko Wijono (Jurnal Maksipreneur, 2013)
The success of a company can be achieved by improving employee performance. To improve employee performance the company must provide motivation or encouragement to employees to perform better by rewarding, recognizing, achieving opportunities, more meaningful work, good working conditions, job security, and salary/wages. From the results of research conducted shows that the motivation of work in the form of Achievement, Recognition, Working Condition, and Wages have a significant influence simultaneously on employee performance. This is evidenced by Fcount greater than Ftable (11.407 > 2.4675). The form of motivation that most affect the employee's performance is Achievement with regression coefficient value of 0.609; and the lowest effect on employee performance is Working Condition with regression coefficient value of 0.305.